The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1039/c5ra14210e
|View full text |Cite
|
Sign up to set email alerts
|

Flexible periodical micro- and nano-structuring of a stainless steel surface using dual-wavelength double-pulse picosecond laser irradiation

Abstract: The picosecond laser-induced ripple formation on a stainless steel surface upon irradiation with linearly-polarized single-pulse and dual-wavelength cross-polarized double-pulse trains in air was studied experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 55 publications
(81 reference statements)
1
13
0
Order By: Relevance
“…In real situations, it can be larger for the electrons and, as mentioned above, is changing in time; 3. The system was linearized, i.e., only the terms proportional to the perturbation amplitude are kept while higher-order terms are neglected in the system (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In real situations, it can be larger for the electrons and, as mentioned above, is changing in time; 3. The system was linearized, i.e., only the terms proportional to the perturbation amplitude are kept while higher-order terms are neglected in the system (5).…”
Section: Discussionmentioning
confidence: 99%
“…Short and ultrashort laser pulses are known to generate LIPSS (Laser Induced Periodic Surface Structures) or ripples on the surfaces of metals, dielectrics and semiconductors. The pattern appears if the surface is exposed to multiple [1,2] or even single [3][4][5] laser shots.…”
Section: Introductionmentioning
confidence: 99%
“…For multi-pulse irradiation regimes, it was argued that the plasmonic stage, which governs the laser-induced periodic surface structures’ orientation, does not necessarily determine the periodicity of the final pattern due to the contribution of thermocapillary effects [119]. The hydrodynamic processes can be more and more important in the formation of the periodic surface structures at high laser fluence for which the metal melting and ablation depths are larger [120,121]. From an experimental point of view, Maragkaki et al [109] produced the laser-induced periodic surface structures on a Cu (bulk target) polished surface at three different wavelengths (355, 532, 1064 nm) of a laser pulse with a duration of 7 ns.…”
Section: Nanostructuration Of Thin Metal Films By Picosecond Pulsementioning
confidence: 99%
“…For multi-pulse irradiation regimes, it was concluded that the plasmonic stage, which governs the LIPSS orientation, does not necessary determine the periodicity of the final pattern due to contribution of the thermocapillary effects [15]. The hydrodynamic processes can be even more important for the LIPSS produced by single laser pulses at relatively high fluences assuming relatively deep melting and strong ablation of material [16,17]. Additionally, the hydrodynamic theory is supported by the topology of the pattern, which can be transient between the LIPSS and cell-like structures [17], that is typical for the hydrodynamic systems.…”
Section: Introductionmentioning
confidence: 99%